HERMENEUTIKA HADIS-HADIS HUKUM FAZLUR RAHMAN - Heru Susanto (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
Fazlur Rahman offered a new methodology in understanding the hadith which he called situational interpretation. This interpretation combines historical and sociological approaches. According to him, the sunnah of the Prophet is more appropriate if viewed as a concept of protection (a general umbrella concept) rather than as a special handle that is absolutely specific. The concept of sunnah and evolution, according to him, includes three categories, ideal sunnah, namely sunnah (practical traditions) and hadith (verbal traditions) which exist together and have the same substance and are attributed to the Prophet and obtain normativeity from him; Second, is the living tradition; and Third, are conclusions drawn from both. The concept of the Sunnah underwent evolution in three periods, firstly, an informal hadith; second, the semi-formal hadith; and third is the formal hadith. This third period causes the actual creative and dynamic sunnah to change into something static, undeveloped and closed.